2021
DOI: 10.1155/2021/1690421
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Levels of IL-13, TGF-β1, and Periostin as Potential Biomarker for Coronary Artery Disease with Acute Heart Failure

Abstract: Objective. Coronary artery disease (CAD) and associated comorbidities such as heart failure (HF) remain the leading cause of morbidity and mortality worldwide, attributed to, at least partially, the lack of biomarkers for efficient disease diagnosis. The study intended to explore potential biomarkers for predicting the presence of HF in CAD patients. Methods. According to the presence of HF, 83 CAD patients with HF were assigned to the AHF group and 52 CAD patients without HF to the CAD group. Additionally, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
7
2
Order By: Relevance
“…Although there have been no prior studies on POSTN in fetal diseases or its expression in GS and AF, many studies have reported differential expression of POSTN (usually up-regulated) in heart valvulogenes [ 13 ], myocardial fibrosis [ 14 ], coronary artery disease [ 15 ], acute myocardial injury [ 16 ], allergic disease, inflammation, and cancer [ 17 ]. In line with prior research [ 18 ], our study emphasizes the significance of POSTN, a non-structural ECM protein, in influencing cellular behavior, and regulating ECM homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been no prior studies on POSTN in fetal diseases or its expression in GS and AF, many studies have reported differential expression of POSTN (usually up-regulated) in heart valvulogenes [ 13 ], myocardial fibrosis [ 14 ], coronary artery disease [ 15 ], acute myocardial injury [ 16 ], allergic disease, inflammation, and cancer [ 17 ]. In line with prior research [ 18 ], our study emphasizes the significance of POSTN, a non-structural ECM protein, in influencing cellular behavior, and regulating ECM homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased TGF-β1 secretion may not only result in hypertrophic cardiomyocytes by autocrine effects, but also force fibroblast conversion to myofibroblasts in a paracrine manner, leading to fibrosis of the ventricular wall, reduction of the compliance of the ventricular wall, and heart failure. 4 Recently, Qiu et al 5 found that TGF-β1 level was increased in patients with acute heart failure compared with control groups, which demonstrates that circulating TGF-β1 is considered as a potential biomarker for failure.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
“…Recently, Qiu et al 5 found that TGF-β1 level was increased in patients with acute heart failure compared with control groups, which demonstrates that circulating TGF-β1 is considered as a potential biomarker for failure.…”
Section: In Responsementioning
confidence: 99%
“…It decreases together with a reduction in myocardial fibrosis in hearts unloaded both clinically (LVAD) and experimentally in mice (aortic arch de-banding) [ 22 ]. It is also a potential marker biomarker for coronary artery disease with acute heart failure [ 23 ]. Furthermore patients with CAD had higher levels than controls at similar ages (around 63 y).…”
Section: Introductionmentioning
confidence: 99%